2015
DOI: 10.1167/iovs.15-16799
|View full text |Cite
|
Sign up to set email alerts
|

Light Induces Ultrastructural Changes in Rod Outer and Inner Segments, Including Autophagy, in a TransgenicXenopus laevisP23H Rhodopsin Model of Retinitis Pigmentosa

Abstract: Our results indicate that ultrastructural defects in outer and inner segment membranes of bP23H expressing rods differ from those observed in drug-induced apoptosis. We suggest that light-induced retinal degeneration caused by P23H rhodopsin occurs via cell death with autophagy, which may represent an attempt to eliminate the mutant rhodopsin and/or damaged cellular compartments from the secretory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 57 publications
(75 reference statements)
10
32
1
Order By: Relevance
“…In summary, we demonstrated that mislocalized rhodopsin disrupts the PM homeostasis of rod photoreceptors through concomitant lysosome-mediated degradation of IS PM membrane protein, NKA. Lysosome-mediated degradation is associated with various photoreceptor degenerative disorders (Chen et al, 2013;Bogéa et al, 2015;Yao et al, 2018), but the context and consequences of the degradation differ among these diseases. For example, in a light-dependent photoreceptor degeneration model, activation of lysosomes and autophagy is neuroprotective (Chen et al, 2013), but in a mouse model of a class II rhodopsin gene mutation (Sakami et al, 2011(Sakami et al, , 2014, activation exacerbates the photoreceptor degeneration (Yao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we demonstrated that mislocalized rhodopsin disrupts the PM homeostasis of rod photoreceptors through concomitant lysosome-mediated degradation of IS PM membrane protein, NKA. Lysosome-mediated degradation is associated with various photoreceptor degenerative disorders (Chen et al, 2013;Bogéa et al, 2015;Yao et al, 2018), but the context and consequences of the degradation differ among these diseases. For example, in a light-dependent photoreceptor degeneration model, activation of lysosomes and autophagy is neuroprotective (Chen et al, 2013), but in a mouse model of a class II rhodopsin gene mutation (Sakami et al, 2011(Sakami et al, , 2014, activation exacerbates the photoreceptor degeneration (Yao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…9 and 10). Aggresomes are also not observed in rod photoreceptor cells in adRP animal models expressing P23H opsin [20,52,53]. Thus, small aggregates are the likely toxic species rather than aggresomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, autophagy has been found to regulate the ultrastructure and function of photoreceptors and to alter their survival and death [36,37]. Wang et al [38] found that inducing autophagy significantly suppressed light-induced photoreceptor death and photoreceptor neural degeneration through the turnover of toxic rhodopsin.…”
Section: Autophagy In Photoreceptorsmentioning
confidence: 99%